Involvement in illegal acts and with drugs as possibilities to deal with the role of the parental child (Psicologia USP, 2004)
This study intends to comprehend the contribution of family dynamics to the construction of identity in adolescents who have committed illegal acts and are drug addicts living in a situation of poverty and social exclusion. Its approach is based on the Systemic Theory. The qualitative methodology of research-intervention is used with ten adolescents under social-educative committals of semi-liberty and also with their families. The results point out the use of drugs and the practice of illegal acts in adolescence as a means to deal with the role of the parental child, permitting the resolution of the identity crisis.